TEACHERS’ ROLE IN BUILDING STUDENTS’ CHARACTER THROUGH ENGLISH LANGUAGE TEACHING CLASSROOM - Meiva Mutia Rahmi; Rita Erlinda (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Teacher plays an essential role in education process. The success of a learning process in changing students behavior depends on how well the teacher treat the students. The teachers also have to be a good model for the student in every classroom interaction. Teaching English will be meaningful when the teacher can integrate the teaching process into the development of students’ character. When the students behave with proper manner in society, the education process can be said meet the goal of education. Any subject matter in education needs to concern about this issue, especially in English language teaching. The students are not only taught about the linguistic structure of the language but also how their character can be built through the classroom interaction. This paper aims to give an overview about the teachers’ role in building student’s character through English language teaching classroom. It is dealing with what is the nature of character and its importance in education. It also describes the roles of teacher as character educator and how to integrate character education into English language teaching which can be done through some way, such as habituation, integrating character education into English material, cooperative learning in English teaching classroom and Instructional Media of English Teaching. Keywords: Classroom Activities, Character, Character Building, English Language Teaching.“Character isn’t inherited. One builds its daily by the way one thinks and acts, thought by thought, actions by actions (Helen G. Douglas)”